2015
DOI: 10.1002/jmv.24327
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of oxidative DNA damage in cervical cells are correlated with the grade of dysplasia and HPV infection

Abstract: The Human papillomavirus is responsible for the most common sexually transmitted infection and is also known to be an oncogenic virus that is associated with cervical, anogenital, and head-neck cancers. The present study aims to assess whether oxidative DNA damage is correlated with the grade of HPV-related lesions. Moreover, we evaluated clinical data and unhealthy lifestyles to verify their possible influence on the genesis of oxidative DNA damage in cervical cells. We quantified the amount of 8-Oxo-2'-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…The increase in OS and DNA damage in C33A cells due to E1/E2 could resemble the results obtained by De Marco et al 42 and Visalli et al 43 , who demonstrated the presence of high levels of ROS and DNA damage in dysplastic tissues, where it is known that E1 and E2 are highly expressed. Our results also show that the co-expression of E6/E7 oncogenes produced a balance in the redox state, which could partially explain the reduction of ROS with no DNA damage in cancer tissues, where E6 and E7 are overexpressed.…”
Section: Discussionsupporting
confidence: 87%
“…The increase in OS and DNA damage in C33A cells due to E1/E2 could resemble the results obtained by De Marco et al 42 and Visalli et al 43 , who demonstrated the presence of high levels of ROS and DNA damage in dysplastic tissues, where it is known that E1 and E2 are highly expressed. Our results also show that the co-expression of E6/E7 oncogenes produced a balance in the redox state, which could partially explain the reduction of ROS with no DNA damage in cancer tissues, where E6 and E7 are overexpressed.…”
Section: Discussionsupporting
confidence: 87%
“…Actually, even if we did not obtain a significative statistical correlation between smoking habit and oral infection, probably because the studied women were occasional smokers, it cannot be excluded a possible synergy between these two factors. This hypothesis is suggested by the well known oxidative damage caused by smoke that is an important risk factor for the HPV infection as previously shown [26]. …”
Section: Discussionmentioning
confidence: 82%
“…Oxidative DNA damage is an inevitable consequence of cellular metabolism and is increased following toxic insult. 8-OHdG is an established cancer biomarker of oxidative stress (64): elevated levels of 8-OHdG were reported in invasive ductal carcinoma (65), primary breast cancer (66), and colorectal cancer (67) compared to normal cells of the corresponding organ, and in precancerous lesions of the cervix compared to normal cervical epithelial cells (68,69). Assessing the impact of the cervical microbiota on 8-OHdG levels is important to understand the role of microbial community composition and oxidative stress in the progression of HPV-related cervical lesions.…”
Section: Discussionmentioning
confidence: 99%